Empowerment of Msme Actors in Lontar Village Through Packaging Skills to Increase The Selling Value of Products - Devi Rahnjen Wijayadne; Sri Nathasya Br Sitepu; Gladys Greselda Gosal; Irantha Hendrika Kenang; Bernard Realino Danu Kristianto; Eddrick Christian Chang; Chantika Dzakiyah Berliana; Qaissa Religia Putri Maharani (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economy; however, many MSME products remain less competitive due to inadequate packaging quality, as commonly found in Lontar Village, Surabaya, where packaging tends to be simple, minimally informative, and lacking clear product identity, which negatively affects consumer perception and market competitiveness. This study aims to empower MSME actors in Lontar Village by enhancing their knowledge and skills in designing and implementing professional, functional, and market-oriented product packaging to increase product selling value. The activity employed a participatory workshop and mentoring approach involving ten MSME actors selected through purposive sampling, with data collected through observation, documentation, and evaluation of packaging conditions before and after the activity and analyzed using a qualitative descriptive method. The results indicate an improvement in participants’ understanding of packaging as a strategic marketing tool, along with enhancements in visual design, completeness of packaging information, material suitability, and overall packaging functionality, demonstrating that the training and mentoring process effectively strengthened both technical skills and strategic awareness of packaging in shaping product image and competitiveness. These findings suggest that practical and contextual packaging empowerment programs can enhance MSME readiness to compete in local and modern markets and serve as a strategic entry point for sustainable MSME development policies.Usaha Mikro, Kecil, dan Menengah (UMKM) memiliki peran strategis dalam perekonomian Indonesia; namun, banyak produk UMKM yang masih kurang kompetitif akibat kualitas kemasan yang belum memadai, sebagaimana ditemukan di Kelurahan Lontar, Surabaya, di mana kemasan produk cenderung sederhana, minim informasi, dan tidak memiliki identitas produk yang jelas sehingga berdampak pada rendahnya persepsi konsumen serta daya saing produk di pasar. Penelitian ini bertujuan untuk memberdayakan pelaku UMKM di Kelurahan Lontar melalui peningkatan pengetahuan dan keterampilan dalam merancang serta menerapkan kemasan produk yang profesional, fungsional, dan berorientasi pasar guna meningkatkan nilai jual produk. Kegiatan ini menggunakan pendekatan workshop partisipatif dan pendampingan yang melibatkan sepuluh pelaku UMKM yang dipilih melalui purposive sampling, dengan data dikumpulkan melalui observasi, dokumentasi, dan evaluasi kondisi kemasan sebelum dan sesudah kegiatan, kemudian dianalisis menggunakan metode deskriptif kualitatif. Hasil penelitian menunjukkan adanya peningkatan pemahaman peserta mengenai kemasan sebagai alat pemasaran strategis, disertai peningkatan pada desain visual, kelengkapan informasi kemasan, kesesuaian bahan, serta fungsi kemasan secara keseluruhan, yang menunjukkan bahwa proses pelatihan dan pendampingan efektif dalam memperkuat keterampilan teknis sekaligus kesadaran strategis mengenai pentingnya kemasan dalam membentuk citra dan daya saing produk. Temuan ini menunjukkan bahwa program pemberdayaan kemasan yang praktis dan kontekstual dapat meningkatkan kesiapan UMKM untuk bersaing di pasar lokal maupun modern serta menjadi titik masuk strategis bagi kebijakan pengembangan UMKM yang berkelanjutan.